Diaryl pyrimidine guanidine suppresses hepatocellular carcinoma cell stemness by targeting β-catenin signaling - Chen, Xuechun; Ni, Dongxuan; Cheng, Jinghui; Liang, Bin; Zhang, Ruihan; Xiao, Weilie; Liu, Rong (Frontiers in Oncology, 2025)
BackgroundLiver cancer remains a major global health burden, with hepatocellular carcinoma (HCC) accounting for approximately 80% of liver cancer cases. Cancer stem cells (CSCs) play a critical role in HCC initiation, progression, metastasis, and resistance to therapy, making them critical targets for novel therapeutic interventions. However, effective agents specifically targeting CSCs in HCC remain limited. The objective of this study was to identify and characterize novel small molecules that inhibit CSCs properties and overcome drug resistance in HCC.MethodsFunctional assays assessed the effects of C504244 on tumor sphere formation, cancer cell proliferation, and migration. RNA sequencing was conducted on C504244-treated HCC cells to investigate changes in gene expression profiles. Downstream targets of the Wnt signaling pathway were analyzed to determine pathway inhibition. Co-immunoprecipitation (Co-IP) was performed to assess whether C504244 disrupts the interaction between β-catenin and Transcription Factor 4 (TCF4) in HCC cells. Lenvatinib-resistant HCC cell lines were used to evaluate the combinatorial efficacy of C504244 and Lenvatinib in vitro and in vivo.ResultsC504244 significantly suppressed tumor sphere formation, proliferation, and migration of HCC cells. Transcriptome analysis revealed that C504244 treatment led to significant inhibition of the Wnt signaling pathway, with corresponding downregulation of downstream target gene expression. Mechanistically, C504244 disrupted the β-catenin/TCF4 complex formation, which may contribute to reduced transcriptional activity. Since β-catenin signaling is hyperactivated in Lenvatinib-resistant HCC cells, C504244 was tested in combination with Lenvatinib and found to markedly sensitize these resistant cells to Lenvatinib treatment both in vitro and in vivo.ConclusionsC504244 represents a promising agent that effectively inhibits β-catenin signaling, thereby impairing CSCs properties and reversing Lenvatinib resistance in HCC cells. These findings suggest that C504244 may serve as a potential therapeutic agent for HCC.